Indonesian Efl Learners’ English Language Learning and use in Social Media: A Case Study - Ilmita, Arnisa Nur; Setyaningsih, Endang; Putra, Kristian Adi (FKIP - Universitas Riau, 2025)
In 2022, Instagram became Indonesia's second most popular social media platform. The most significant portion of users, around 31 percent, were youth in the 18 to 24 age range. This study aims to examine EFL learners' language learning practices on Instagram and characterize the utilization of English on various sides of social media activities on Instagram among youth Indonesians. A qualitative analysis used a case study method, to explore the intricate dynamics of language self-learning on Instagram. Answering the first research questions, the findings show the use of Instagram to study English conducted through several activities, including following English learning accounts, joining the broadcast channel of the English learning community, and watching English learning content on FYP “For You Page.” Furthermore, in answering the second research question, the findings show that using English on Instagram can be done through several activities, including creating English-related content, writing English as a caption, and engaging in English interactions. The study contributes to understanding how EFL learners' online informal language learning adapts to social media like Instagram.